2018
DOI: 10.3389/fphys.2018.01378
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of BOLD Time Series in a Network Associated With Waiting Impulsivity

Abstract: Fractal phenomena can be found in numerous scientific areas including neuroscience. Fractals are structures, in which the whole has the same shape as its parts. A specific structure known as pink noise (also called fractal or 1/f noise) is one key fractal manifestation, exhibits both stability and adaptability, and can be addressed via the Hurst exponent (H). FMRI studies using H on regional fMRI time courses used fractality as an important characteristic to unravel neural networks from artificial noise. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 91 publications
(164 reference statements)
0
26
0
Order By: Relevance
“…The posterior cingulate cortex has been suggested to be a key region that links distinct functional networks to enable efficient cognitive function, in particular, working memory and focused attention [45]. One fMRI study that addressed the functional correlates of waiting impulsivity in HC showed the discriminative activity of middle frontal gyrus between subjects with high and low waiting impulsivity [46]. Further large-scale studies will be warranted to address the potential role of clinical and neurobiological heterogeneity of TD on task performance and network dysfunction in light of recent findings suggesting that brain networks are differentially altered in adults and children with TD [47].…”
Section: Discussionmentioning
confidence: 99%
“…The posterior cingulate cortex has been suggested to be a key region that links distinct functional networks to enable efficient cognitive function, in particular, working memory and focused attention [45]. One fMRI study that addressed the functional correlates of waiting impulsivity in HC showed the discriminative activity of middle frontal gyrus between subjects with high and low waiting impulsivity [46]. Further large-scale studies will be warranted to address the potential role of clinical and neurobiological heterogeneity of TD on task performance and network dysfunction in light of recent findings suggesting that brain networks are differentially altered in adults and children with TD [47].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that the noise obtained from the scanner (e.g. pink noise or 1/f noise) might be flattened out when concatenating multiple scans together (Afshinpour et al, 2008;Akhrif et al, 2018). When a single long scan is acquired, however, the noise is maintained as the main variation between test and retest sessions, thereby reducing reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of H occurred during the task performance in comparison to resting state (He, 2011;Ciuciu et al, 2012). Moreover, H changed in healthy aging (Suckling et al, 2008;Dong et al, 2018), personal traits as impulsivity (Hahn et al, 2012;Akhrif et al, 2018), and mental disease, such as major depressive disorder (Wei et al, 2013), schizophrenia (Sokunbi et al, 2014) and Alzheimer's disease (Maxim et al, 2005).…”
Section: Introductionmentioning
confidence: 98%